2017
DOI: 10.1037/neu0000336
|View full text |Cite
|
Sign up to set email alerts
|

The impact of phenylalanine levels on cognitive outcomes in adults with phenylketonuria: Effects across tasks and developmental stages.

Abstract: Objective: Phenylketonuria (PKU) is due to an inability to metabolize the amino acid phenylalanine (Phe), leading to its accumulation in the brain. Phe levels can be controlled following a protein-free diet, but cognitive impairments are still present. A number of questions remain to be answered related to which type of metabolic control is important, the age when it is important, the cognitive functions which are most affected and, the best tests to use to monitor cognitive health. Method: We investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
94
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(118 citation statements)
references
References 58 publications
9
94
0
4
Order By: Relevance
“…Nevertheless, neurocognitive deficits have still been reported in individuals with PKU treated who were treated early and continuously with a phenylalanine-restricted diet. related to cognitive outcome in early and continuously treated PKU (15)(16)(17). We saw the well-known negative correlation of IQ with concurrent blood phenylalanine level in those patients in our study who had classic PKU.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Nevertheless, neurocognitive deficits have still been reported in individuals with PKU treated who were treated early and continuously with a phenylalanine-restricted diet. related to cognitive outcome in early and continuously treated PKU (15)(16)(17). We saw the well-known negative correlation of IQ with concurrent blood phenylalanine level in those patients in our study who had classic PKU.…”
Section: Discussionsupporting
confidence: 59%
“…Nevertheless, neurocognitive deficits have still been reported in individuals with PKU treated who were treated early and continuously with a phenylalanine‐restricted diet. According to Anastasoaie et al, Hood et al and Romani et al, the stability of blood phenylalanine levels may be related to cognitive outcome in early and continuously treated PKU .…”
Section: Discussionmentioning
confidence: 99%
“…The association of Phe levels with adult cognition may depend on the age at which metabolic control was measured and on the particular cognitive domain examined. A recent study showed that performance on verbal memory and learning, visuomotor coordination and sustained attention were better predicted by recent Phe levels than control during childhood, whereas performances on visuospatial processing and complex executive functions showed a stable association with metabolic control across different ages . Interestingly, a positive correlation has been found between striatal dopamine D 2/3 R receptor availability, with impulsivity and error rate in a cognitive flexibility task, while there was no correlation with working memory or inhibitory control.…”
Section: Iq and Neuropsychological Outcomesmentioning
confidence: 99%
“…A number of well‐controlled studies reported statistically significant deficits in patients compared with healthy control groups or normative populations across a range of neuropsychological and executive functions, including sustained and selective attention, working memory, response inhibition, and letter fluency . Two studies that performed extensive analyses on the same cohort of patients reported impairments in patients with ETPKU vs healthy controls, in the higher order executive functions, visuo‐spatial attention and visuo‐motor coordination, with significant variability across patients . Additionally, a recent study reported that compared with a control group, patients with ETPKU showed deficits in complex language tasks and were slower and less accurate in tasks requiring planning and strategic abilities .…”
Section: Iq and Neuropsychological Outcomesmentioning
confidence: 99%
“…The diagnosis and follow-up of PKU patients largely relies on the plasma concentration of phenylalanine in combination with the ratio of Phe to Tyr. However, adequate biochemical control of Phe levels does not directly translate into the desired clinical outcome (Romani et al 2017 andJahja et al 2017). For HMGCLD 3-hydroxyisovaleric acid, 3-hydroxyisovalerylcarnitine, 3-methylglutaconic acid, 3-hydroxy-3-methylglutaric acid, 3-methylcrotonylglycine, 3methylglutaric acid, and 3-methylglutarylcarnitine are known accumulating compounds.…”
Section: Communicated By: Nenad Blaumentioning
confidence: 99%